2002
DOI: 10.1046/j.1365-2141.2002.03475.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic large cell lymphoma of the parietal bone

Abstract: A 16-year-old youth was referred to our hospital for evaluation of a scalp lesion associated with cervical lymphadenopathy. Six months previously he had presented elsewhere with painful cervical lymphadenopathy and fever. A biopsy of the lymph node was inconclusive. On presentation to us he had a bald scalp area over a deeply infiltrating tumour mass. Cranial magnetic resonance imaging showed a densely enhancing, mushroom-like soft-tissue mass involving the pericranium, the aponeurotic coverings (left) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…ALCL represents about 10-15% of NHL in children [2]. It generally arises dominal or mediastinal lymph nodes; primary bone and CNS involvement is ver After a review of English literature, we identified 17 cases of pediatric prim ALCL (Table 2) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The median age of onset was 10 years and 82% (14/17) we Multifocal and unifocal bone lesions were identified in 7 (41%) and 10 (59%) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALCL represents about 10-15% of NHL in children [2]. It generally arises dominal or mediastinal lymph nodes; primary bone and CNS involvement is ver After a review of English literature, we identified 17 cases of pediatric prim ALCL (Table 2) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The median age of onset was 10 years and 82% (14/17) we Multifocal and unifocal bone lesions were identified in 7 (41%) and 10 (59%) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…After a review of English literature, we identified 17 cases of pediatric primary bone ALCL (Table 2) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The median age of onset was 10 years and 82% (14/17) were male.…”
Section: Discussionmentioning
confidence: 99%